(untitled) (Fiep Bulletin - online, 2013)
The purpose of this investigation is expressed by its title: Corporal composition and conditional capacity in high school children in public schools in the city of Armenia, we focus on the quantitive-explanation, in a descriptive, study correlacional and transversal. Court in the population of 23.212 students, we evaluated a representative survey of 1.150, with a level of 95% estimated error of 3%. We used functional test for the conditional training and the protocol of the international Society for the Advancement of Kinanthropometry(ISAK). Following we digited the information in excel XP2007 were we calculated an average, deviation standard (DS) and correlation. The results show that in the average was of (48,66 kg) in the men of (49,35kg) and in the women (47,98 kg). For the size was of (170 cm), for the men (158cm) and the women (153cm). In the case of the physical training for the flexibility the average was (2,26cm) for the men (1,34cm) and women (3,09cm); in the strength the average was of (149,68cm) in the women (129,26cm) and the men (173,14cm); in the aceleration the average was of (4,70sg) in men (4,53sg) and the women (4,85sg) and the resistant variety the data was (41,59Vo2) the men (45,65Vo2) and the woman (38,05Vo2). it is concluded that the aerobic capacity, the strength and the flexibility in the objective population, present low development in comparison with the national and international index.